Pre-diagnosis Dairy Product Intake and Ovarian Cancer Mortality: Results From the Ovarian Cancer Follow-Up Study (OOPS) - Jiang, Luo; Gong, Ting-Ting; Gao, Song; Li, Xiu-Qin; Liu, Fang-Hua; Wen, Zhao-Yan; Wei, Yi-Fan; Yan, Shi; Hou, Rui; Wu, Qi-Jun (Frontiers in Nutrition, 2021)
Background: Dairy product consumption is associated with ovarian cancer (OC) incidence. However, limited evidence is available on its influence on OC mortality. Methods: The association between pre-diagnostic dairy product intake and OC mortality was investigated in the OC follow-up study, which included a hospital-based cohort (n = 853) of women diagnosed with epithelial OC between 2015 and 2020. Pre-diagnosis diet information was collected using a validated food frequency questionnaire. Deaths were ascertained up to March 31, 2021 via death registry linkage. Cox proportional hazards model was used to estimate the adjusted hazard ratio (HR) and 95% confidence interval (CI) for the aforementioned association. Results: A total of 130 women died during the median follow-up of 37.2 months (interquartile: 24.7–50.2 months). Comparisons of highest to lowest tertile intake showed that pre-diagnosis dairy product use was associated with total OC mortality (HR = 2.03, 95% CI = 1.21–3.40, p trend = 0.06). In addition, short survival was separately associated with protein (HR = 2.09, 95% CI = 1.25–3.49, p trend < 0.05), fat (HR = 2.16, 95% CI = 1.3–3.61, p trend < 0.05), and calcium (HR = 2.03, 95% CI = 1.21–3.4, p trend = 0.06) from dairy intake. Similar positive magnitudes were observed for menopausal status, residual lesions, histological type, and body mass index, although not all of these factors showed statistical significance. Conclusion: Pre-diagnosis dairy product consumption, including protein, fat, and calcium from dairy intake, was associated with higher mortality among OC survivors.